Kegagalan Pendiri PT Melakukan Penyetoran Modal: Studi Kasus PT MBB Conggeang - Jatiningsih, Prima Yulia; Dewi, Yetty Komalasari (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
The research objectives are first, to analyze the founders who do not deposit capital as shareholders according to UU No. 40 Tahun 2007 (UUPT); secondly, analyzing the legal consequences of Perkumpulan BUM Desa Bersama Conggeang as the founder who did not deposit capital while PT MBB Conggeang was established. This research is applied by normative juridical with statute, comparative, and case study approach. The research concludes that founders who do not deposit paid-up capital cannot qualify as shareholders as referred to in the UUPT. This is because taking part in shares and making a full deposit is a dwingen recht as stipulated in Article 33 paragraph (1) and (2) UUPT. In addition, recording in the register of shareholders after the capital is deposited becomes a requirement for founders to be able to exercise their rights as shareholders in accordance with Article 52 UUPT. As for the legal consequences of the Perkumpulan BUM Desa Bersama Conggeang as the founder who did not deposit capital, they did not have the right to attend and vote at the general meeting of PT MBB Conggeang, including receiving dividends if the PT MBB Conggeang decided to distribute dividends.